Effect of Ammonium and Nitrate on Ferric Chelate Reductase and Nitrate Reductase in Vaccinium Species - POONNACHIT, U. (Ann Bot, 2004)
• Background and Aims Most Vaccinium species have strict soil requirements for optimal growth, requiring low pH, high iron availability and nitrogen primarily in the ammonium form. These soils are limited and are often located near wetlands. Vaccinium arboreum is a wild species adapted to a wide range of soils, including high pH, low iron, and nitrate‐containing soils. This broader soil adaptation in V. arboreum may be related to increased efficiency of iron or nitrate uptake compared with the cultivated Vaccinium species. • Methods Nitrate, ammonium and iron uptake, and nitrate reductase (NR) and ferric chelate reductase (FCR) activities were compared in two Vaccinium species grown hydroponically in either nitrate or ammonia, with or without iron. The species studied were the wild V. arboreum and the cultivated V. corymbosum interspecific hybrid, which exhibits the strict soil requirements of most Vaccinium species. • Key Results Ammonium uptake was significantly greater than nitrate uptake in both species, while nitrate uptake was greater in the wild species, V. arboreum, compared with the cultivated species, V. corymbosum. The increased nitrate uptake in V. arboreum was correlated with increased root NR activity compared with V. corymbosum. The lower nitrate uptake in V. corymbosum was reflected in decreased plant dry weight in this species compared with V. arboreum. Root FCR activity increased significantly in V. corymbosum grown under iron‐deficient conditions, compared with the same species grown under iron‐sufficient conditions or with V. arboreum grown under either iron condition. • Conclusions. V. arboreum appears to be more efficient in acquiring nitrate compared with V. corymbosum, possibly due to increased NR activity and this may partially explain the wider soil adaptation of V. arboreum.